Exploring the role of advanced clinical practitioners (ACPs) and their contribution to health services in England: A qualitative exploratory study. (February 2023) - Mann, Claire; Timmons, Stephen; Evans, Catrin; Pearce, Ruth; Overton, Charlotte; Hinsliff-Smith, Kathryn; Conway, Joy
Abstract: Background: An extended role being explored globally is the advanced clinical practitioner (ACP). In England this is an extended role for allied health professions, nurses and midwives in a range of settings. Objectives: This paper focuses on three research questions: 1) What is the role of ACPs in England? 2) What are the barriers and facilitators to implementing the role? and 3) What is the contribution of ACPs to health services in England? Design/setting: A qualitative, exploratory study to explore perspectives on the ACP role in a range of clinical settings. Participants: We recruited 63 stakeholders, including 34 nurses, working in a ACP role or ACP education. A purposive snowball sampling technique identified participants meeting inclusion criteria. Methods: One-to-one semi-structured interviews throughout 2020, recorded and transcribed verbatim, anonymised and thematically analysed. Results: The ACP role in England was undertaken in a broad range of clinical contexts. In England 'advanced clinical practitioner' was not a protected title. There were high levels of variability and ambiguity of understanding and deployment of the ACP role in England. Facilitators to the implementation process included training and education, clinical supervision and organisational support. Lack of protection for the role and variances in experience were barriers. Employer support facilitated development of the ACP role, however where support was limited, at either an individual or organisation level, this was a barrier. Our study highlighted the wide range of ways the ACP role benefitted patient outcomes and workforce development. Conclusions: This study outlines the contribution that ACPs can make to health services, contributing factors and key barriers and facilitators to implementing this role. The work showed the positive contribution ACPs can make to service redesign, workforce development and patient outcomes, whilst accepting there is much work to do to ensure protected status and parity across all professions and clinical contexts